Draft genome sequence of a novel actinobacterium from the family Intrasporangiaceae isolated from Signy Island, Antarctica - Thomas, S.M.; Convey, Peter; Gan, Han Ming; Pearce, David Anthony; Tan, Geok Yuan Annie (Indian Academy of Sciences, 2018)
Actinobacterium strain S63T isolated from a soil sample collected from Spindrift Col on Signy Island (South Orkney Islands, maritime Antarctic) is a new species of the Intrasporangiaceae family. Here we report a draft genome sequence with an approximate size of 5 Mbp contained in 54 contigs (69.33% GC content). Preliminary analysis revealed the presence of cold active protein coding sequences, which may indicate an adaptation to the harsh polar environment from which the strain was isolated.